D6: The product rule
What is the product rule? It is useful when you want to differentiate a function that comprises one function multiplied by another function.
The derivatives of functions such as \(y=f(x)=2x\sin\left(x\right)\) and \(y=f(x)=xe^{x}\) can be found using the product rule.
Definition
If \[\begin{align*} y & =f\left(x\right)\\ & =u\left(x\right)\cdot v\left(x\right) \end{align*}\] then \[\begin{align*} y' & =f'\left(x\right)\\ & =u\left(x\right)\cdot v'\left(x\right)+u'\left(x\right)\cdot v\left(x\right). \end{align*}\] This is often abbreviated to \[\begin{align*} y' & =uv'+u'v. \end{align*}\]
VIDEO
Hi, I’m Martin Lindsay from the Study and Learning Centre at RMIT University. This is a short movie on the product rule.
The product rule is used when we want to differentiate the product of two functions. So, if f of x, is equal to u of x times v of x, then the derivative f dash x is u of x times v dash x plus u dash x times vx. This formula can be abbreviated to y dash is equal to u times v dash, plus v times u dash. Note also that f dash x and y dash mean the same thing. So lets do a couple of examples to illustrate the product rule. Here’s a function, x plus 3 to the power of six multiplied by 2x minus 1. Notice here that there are two functions so we can use the product rule. So, let u equal x plus 3 to the power of 6, therefore the derivative is u dash equals 6 brackets x plus 3 to the power of five and let v equals 2x minus 1, and the derivative there is v dash equals 2. Notice I’ve used the chain rule to work out u dash. Substituting in to the formula y dash equals uv dash plus vu dash I get the following four lines of working. Notice when you get down to the third line that I’ve taken a factor of 2 brackets x plus 3 to the power of 5 out, and in the last line I’ve simplified the expression inside the square brackets to give us an answer of 14x brackets x plus 3 all to the power of 5.
Here’s another example. Again notice that there are two functions here e to the x multiplied by sin of 2x. So, this lends itself to the product rule. So I’m letting u equals e to the x, the derivative is the same e to the x and v equals sin of 2 x from which the derivative is 2 cos of 2 x using the chain rule. Substituting as before into the formula y dash equals uv dash plus vu dash I get the following three lines of working. Notice again always look for terms that will factorise and I’ve done that in the last line. So my answer is y dash is equal to ex brackets 2 cos 2x plus sin of 2 x.
Now try some questions for yourself. The answers to these questions are on the next slide. Thanks for watching this short movie.
Examples
Find the derivative of \(f(x)=\left(x+3\right)^{6}\left(2x-1\right).\)
Solution:
Let \(u=(x+3)^{6}\) and \(v=2x-1,\) then using the chain rule1 Let \(w=x+3\) then \(u=w^{6}\) and \[\begin{align*} u' & =\frac{du}{dw}\times\frac{dw}{dx}\\ & =6w^{5}\cdot1\\ & =6\left(x+3\right)^{5}. \end{align*}\] \[\begin{align*} u' & =6(x+3)^{5} \end{align*}\] and \[\begin{align*} v' & =2. \end{align*}\] Hence, using the product rule,
\[\begin{align*} \textrm{}y' & =uv'+u'v\\ & =\left(x+3\right)^{6}\cdot2+6\left(x+3\right){}^{5}\left(2x\text{\textendash}1\right)\\ & =(x+3)^{5}\left[2\left(x+3\right)+6\left(2x-1\right)\right]\\ & =14x(x+3)^{5}. \end{align*}\]
Differentiate \(e^{x}\sin\left(2x\right).\)
Solution:
Let \(u=e^{x}\) and \(v=\sin\left(2x\right),\) then \[\begin{align*} u' & =e^{x}\\ v' & =2\cos\left(2x\right) \end{align*}\] where we have used the chain rule to evaluate \(v'.\) 2 Let \(w=2x\) then \(v=\sin\left(w\right)\) and \[\begin{align*} v' & =\frac{dv}{dw}\times\frac{dw}{dx}\\ & =\cos\left(w\right)\cdot2\\ & =2\cos\left(2x\right). \end{align*}\] Hence, using the product rule,
\[\begin{align*} y' & =uv'+u'v\\ & =e^{x}\cdot2\cos\left(2x\right)+e^{x}\sin\left(2x\right)\\ & =2e^{x}\cos\left(2x\right)+e^{x}\sin\left(2x\right)\\ & =e^{x}\left(2\cos\left(2x\right)+\sin\left(2x\right)\right). \end{align*}\]
Exercises
Use the product rule to differentiate the following
\(\text{$\qquad$ a) }\) \(y\) \(=\left(x-2\right)\left(6x+7\right)\textrm{ and}\) simplify as far as possible.
\(\text{$\qquad$ b) }\) \(f(x)=\left(2x^{2}+4\right)\left(x^{5}+4x^{2}-2\right)\) (do not simplify).
\(\text{$\qquad$ c) }\) \(y=\left(\sqrt{x}-1\right)\left(x^{2}+1\right)\)
\(\text{$\qquad$ d) }\) \(y=\left(x^{3}-4x+\sqrt{x}\right)\left(3x^{4}+2\right).\)
(Note that answers may be written differently)
\(\text{$\qquad$ a) }\) \(12x-5\)
\(\text{$\qquad$ b) }\) \(\left(2x^{2}+4\right)\left(5x^{4}+8x\right)+4x\left(x^{5}+4x^{2}-2\right)\)
\(\text{$\qquad$ c) }\) \(\frac{5}{2}x^{3/2}-2x+\frac{1}{2\sqrt{x}}\)
\(\text{$\qquad$ d) }\) \(12x^{3}\left(x^{3}-4x+\sqrt{x}\right)+\left(3x^{4}+2\right)\left(3x^{2}-4+\frac{1}{2\sqrt{x}}\right)\)
Find the derivative of
\(\qquad\text{a)}\) \(y=e^{x}\tan x\)
\(\qquad\text{b)}\) \(y=x^{2}\log_{e}x\)
\(\qquad\text{c)}\) \(y=\sin x\cos x\)
\(\qquad\text{d)}\) \(y=\frac{e^{x}}{x}\) \(\textrm{Hint}:\frac{1}{x}=x^{-1}.\)
(Note that answers may be written differently)
\(\qquad\text{a)}\) \(e^{x}\tan x+e^{x}\sec^{2}x\)
\(\qquad\text{b)}\) \(x+2x\log_{e}x\)
\(\qquad\text{c)}\) \(\cos^{2}\left(x\right)-\sin^{2}\left(x\right)\)
\(\qquad\text{d)}\) \(\frac{e^{x}}{x}-\frac{e^{x}}{x^{2}}=e^{x}\left(\frac{1}{x}-\frac{1}{x^{2}}\right)\)
Images on this page by RMIT , licensed under CC BY-NC 4.0
Copy the iframe code above.
Go to the course in Canvas where you want to add the content.
Navigate to the page or module where you want to embed the content.
In the Rich Content Editor, click on the "HTML Editor" link.
Paste the iframe code into the HTML area.
Switch back to the Rich Content Editor to see the embedded content.
Save the changes to your page or module.
Note: Ensure that your permissions allow embedding external content in your Canvas LMS instance.